ASHERAH AND APHRODITE: A COINCIDENCE?*. (2nd April 2015) - Jacobson, Howard
Abstract : It has long been known that there is a significant connection between Aphrodite and Semitic goddesses. In Walter Burkert's recent words, 'Behind the figure of Aphrodite there clearly stands the ancient Semitic goddess of love, Ishtar-Astarte.' This was already recognized by Herodotus (1.105, 131) and Philo of Byblos (Eus. Prep. evang. 1.812). I want here to note a curious and striking item of connection that has not been noticed.